2005
DOI: 10.1016/j.cell.2005.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer between Cytochrome c and p66Shc Generates Reactive Oxygen Species that Trigger Mitochondrial Apoptosis

Abstract: Reactive oxygen species (ROS) are potent inducers of oxidative damage and have been implicated in the regulation of specific cellular functions, including apoptosis. Mitochondrial ROS increase markedly after proapoptotic signals, though the biological significance and the underlying molecular mechanisms remain undetermined. P66Shc is a genetic determinant of life span in mammals, which regulates ROS metabolism and apoptosis. We report here that p66Shc is a redox enzyme that generates mitochondrial ROS (hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
956
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,058 publications
(1,005 citation statements)
references
References 36 publications
26
956
0
4
Order By: Relevance
“…A recent study 65 indicated that activated caspase 3 cleaves the p75 subunit of complex I of the mitochondrial electron transport chain, resulting in ROS accumulation. Similarly, Giorgio et al 66 have shown that proapoptotic signals induce release of p66 Shc from a putative inhibitory complex, which in turn oxidizes reduced cytochrome c, thereby generating ROS. On the other hand, Ventura et al 53 have reported that TNFa-induced ROS accumulation is abolished in cells lacking JNK1 and JNK2, indicating that a central role for JNK in ROS accumulation.…”
Section: The Molecular Mechanisms Of Tnfa-induced Ros Accumulationmentioning
confidence: 90%
“…A recent study 65 indicated that activated caspase 3 cleaves the p75 subunit of complex I of the mitochondrial electron transport chain, resulting in ROS accumulation. Similarly, Giorgio et al 66 have shown that proapoptotic signals induce release of p66 Shc from a putative inhibitory complex, which in turn oxidizes reduced cytochrome c, thereby generating ROS. On the other hand, Ventura et al 53 have reported that TNFa-induced ROS accumulation is abolished in cells lacking JNK1 and JNK2, indicating that a central role for JNK in ROS accumulation.…”
Section: The Molecular Mechanisms Of Tnfa-induced Ros Accumulationmentioning
confidence: 90%
“…Most of the p66Shc is located in cytoplasm with a small fraction localized in the mitochondrial intermembrane space. Upon oxidative stress, p66Shc translocates to mitochondrial intermembrane space, where it associates with cytochromec, thus inducing ROS generation [65].…”
Section: Mitochondriamentioning
confidence: 99%
“…P66SHC protein is the largest isoform encoded by the ShcA locus, typical of vertebrates, and it sustains intracellular levels of ROS (Giorgio et al ., 2005 Gertz & Steegborn, 2010) and regulates redox signaling pathways (Frijhoff et al ., 2014), mitochondrial apoptosis (Migliaccio et al ., 2006), and aging (Trinei et al ., 2009). P66SHC null mice (p66SHC −/− ) develop normally and resulted to be protected from aging‐associated diseases, such as atherosclerosis (Martin‐Padura et al ., 2008), diabetes compliances (Menini et al ., 2007), onset (Tomilov et al ., 2011), cognitive decline (Berry et al ., 2007), and neurodegeneration (Savino et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%